Evaluation of Microstructure and Mechanical Properties of a Ti10Mo8Nb Alloy for Biomedical Applications - Capellato, Patricia (2022)
The growth of the elderly population is urging for more suitable biomaterials to allow the performance of better surgical and implant procedures and accelerate the patient’s healing because the elderly are more vulnerable to orthopedic and dental problems. β-phase Ti alloys can improve the mechanical properties of implants by reducing their elastic modulus and, consequently, the effects of stress shielding within bones. Therefore, the objective of this article is to study a novel ternary β-phase alloy of Ti10Mo8Nb produced by an electric arc furnace and rotary forge. The microstructure and mechanical properties of the Ti10Mo8Nb alloy were investigated in order to evaluate its suitability for biomedical applications and compare its characteristics with those present in Ti-alloys commerced or widely researched for prosthetic purposes. A tensile test, Vickers microhardness test, use of microstructure of optical microscopy for examination of microstructure, X-ray diffraction and hemolysis analysis were carried out. Thus, the Ti10Mo8Nb alloy showed suitable properties for biomedical applications, as well as having the potential to reduce the possibility to occur stress shielding after prosthetic implantations, especially for orthopedics and dentistry.